Fire engine drawn by dogteam to a fire in Dawson, Yukon Territory, 1899 - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Fire engine drawn by dogs to fire in Dawson, 1899" Original image in Hegg Album 22, page 4. Klondike Gold Rush.